2014
DOI: 10.1002/adem.201300519
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Piezoelectric Behavior of Polyamide/PZT/CNT Multifunctional Nanocomposites

Abstract: Three-phase polyamide 11 (PA 11)/lead zirconate titanate (PZT)/carbon nanotubes (CNT) composites are elaborated by extrusion. The influence of inorganic particles on the electrical properties of conductive composites and the influence of conductive particles on the ferroelectric properties of organic/inorganic composites are both studied. Inorganic particles do not modify the establishment of the electrical percolation path of CNTs either regarding the percolation threshold value or the conductivity reached ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…It has to be noticed that the nanocomposites must be necessary insulator to be poled. In a previous work, the electrical conductivity of PA 11/PZT/CNT composites was studied [29]. It was shown that for a CNT concentration of 0.2 vol.%, the PA 11/PZT 30 vol.%/CNT 0.2 vol.% is still insulator with an electrical conductivity within the thickness of 1.9 · 10 −12 S·m −1 .…”
Section: Nanocomposite Processingmentioning
confidence: 98%
“…It has to be noticed that the nanocomposites must be necessary insulator to be poled. In a previous work, the electrical conductivity of PA 11/PZT/CNT composites was studied [29]. It was shown that for a CNT concentration of 0.2 vol.%, the PA 11/PZT 30 vol.%/CNT 0.2 vol.% is still insulator with an electrical conductivity within the thickness of 1.9 · 10 −12 S·m −1 .…”
Section: Nanocomposite Processingmentioning
confidence: 98%
“…In 2014, Carponcin et al . prepared a three‐phase multifunctional nanocomposite composed of polyamide 11 (PA 11), PZT, and CNT.…”
Section: Piezoelectric Polymers: a Productive Alternative To Piezo‐cementioning
confidence: 99%
“…In 2014, Carponcin et al [124] prepared a three-phase multifunctional nanocomposite composed of polyamide 11 (PA 11), PZT, and CNT. The authors reported that addition of 0.2 vol% of CNTs resulted in improvement of dielectric permittivity of PA 11/PZT composite.…”
Section: Polyamidesmentioning
confidence: 99%
“…This system includes the other kind of nanoparticle as functional filler except CNTs. The addition of other nanoparticles usually greatly improves the dielectric properties of the whole composite, thus, this system makes nanocomposites attractive for both scientific research and practical applications …”
Section: Cnts/polymer Dielectric Nanocompositesmentioning
confidence: 99%